Ten Simple Rules For Successful And Sustainable African Research Collaboration - Dine, Roseline Dzekem; Elkheir, Lamis Yahia Mohamed; Raimi, Morufu Olalekan; Alemayehu, Micheal; Mohamed, Salem Youssef; Turzin, Justice Kwadwo; Arogundade, Femi Qudus; Ochola, Elizabeth Akinyi; Nasiyo, Alex Mukungu; Mwawanga, Raziah Quallatein; Yabo, Yahaya Abubakar (PLoS Computational Biology, 2024)
This manuscript presents 10 practical and sustainable steps that if followed and built upon will enhance successful collaboration between African researchers and the international research community.
Keywords: Africa; Capacity building; Diversity